Effect of single and combination of three triazine metabolites at environmental concentrations on early life stages of common carp (Cyprinus carpio L.) - Velisek, Josef; Stara, Alzbeta; Zuskova, Eliska (Environmental science and pollution research international, 2016)
The sensitivity of early life stages of common carp (Cyprinus carpio L.) to chronic exposure to single and combined environmental concentrations of the triazine metabolites terbuthylazine 2-hydroxy, terbuthylazine-desethyl and atrazine 2-hydroxy was evaluated under laboratory conditions. Their effects were assessed on lipid peroxidation, antioxidant enzymes (total superoxide dismutase, glutathione reductase, catalase, glutathione S-transferase, reduced glutathione), mortality, growth, development and histology. Single metabolites (terbuthylazine 2-hydroxy-0.73 μg/L; terbuthylazine-desethyl-1.80 μg/L; atrazine 2-hydroxy-0.66 μg/L) and combinations were not associated with negative effects on hatching, behaviour, embryo viability, growth or early ontogeny. Carp exposed to terbuthylazine-desethyl at 1.80 μg/L showed significantly lower total superoxide dismutase and glutathione reductase activity compared with the control group. Liver histology revealed diffused steatosis associated with the presence of lipid inclusions in hepatic cells in groups exposed to terbuthylazine-desethyl, atrazine 2-hydroxy and the tested combination of metabolites.
Keywords: Carps; Glutathione; Superoxide Dismutase; herbicidy; Glutathione Transferase; Terbuthylazine-desethyl; peroxidace lipidů; Oxidative Stress; Antioxidant enzymes; chemické látky znečišťující vodu; Herbicides; Water Pollutants, Chemical; glutathionreduktasa; embryo nesavčí; antioxidancia; Atrazine 2-hydroxy; látky reagující s kyselinou thiobarbiturovou; Embryo, Nonmammalian; superoxiddismutasa; Catalase; Glutathione Reductase; zvířata; játra; glutathion; Triazines; kapři; Terbuthylazine 2-hydroxy; Liver; oxidační stres; Animals; Atrazine; Fish; Thiobarbituric Acid Reactive Substances; glutathiontransferasa; atrazin; triaziny; Antioxidants; Lipid Peroxidation; katalasa